2003
DOI: 10.1104/pp.103.022871
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Profiling in Response to Ultraviolet Radiation in Maize Genotypes with Varying Flavonoid Content  

Abstract: Microarray hybridization was used to assess acclimation responses to four UV regimes by near isogenic maize (Zea mays) lines varying in flavonoid content. We found that 355 of the 2,500 cDNAs tested were regulated by UV radiation in at least one genotype. Among these, 232 transcripts are assigned putative functions, whereas 123 encode unknown proteins. UV-B increased expression of stress response and ribosomal protein genes, whereas photosynthesis-associated genes were down-regulated; lines lacking UV-absorbin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

25
182
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 209 publications
(207 citation statements)
references
References 78 publications
25
182
0
Order By: Relevance
“…In addition, increasing evidence indicates that RPL10 protein from various organisms has multiple extraribosomal functions, besides being a constituent of the ribosome and participating in protein synthesis (Chan et al, 1996;Wool, 1996;Nika et al, 1997;Mills et al, 1999;Chávez-Ríos et al, 2003;Wen et al, 2005). Previously, by transcriptome profiling using different UV-B regimes and maize lines, we found that the functional group with the largest number of genes up-regulated by UV-B light corresponds to proteins involved in protein synthesis, including cytoplasmic ribosomal proteins, initiation and elongation factors, and poly(A)-binding proteins (Casati and Walbot, 2003). Among them, rpl10, a homolog of a human transcript encoding the QM protein, showed increased levels after the UV-B treatments (Casati and Walbot, 2003).…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…In addition, increasing evidence indicates that RPL10 protein from various organisms has multiple extraribosomal functions, besides being a constituent of the ribosome and participating in protein synthesis (Chan et al, 1996;Wool, 1996;Nika et al, 1997;Mills et al, 1999;Chávez-Ríos et al, 2003;Wen et al, 2005). Previously, by transcriptome profiling using different UV-B regimes and maize lines, we found that the functional group with the largest number of genes up-regulated by UV-B light corresponds to proteins involved in protein synthesis, including cytoplasmic ribosomal proteins, initiation and elongation factors, and poly(A)-binding proteins (Casati and Walbot, 2003). Among them, rpl10, a homolog of a human transcript encoding the QM protein, showed increased levels after the UV-B treatments (Casati and Walbot, 2003).…”
Section: Discussionmentioning
confidence: 89%
“…In previous experiments, by microarray analysis, we showed that a maize rpl10 gene is induced by UV-B radiation (Casati and Walbot, 2003). To validate this result, we analyzed the effect of UV-B radiation on the expression of RPL10 genes in maize and Arabidopsis plants by qRT-PCR.…”
Section: Regulation Of Rpl10 Expression By Uv-b Lightmentioning
confidence: 85%
See 2 more Smart Citations
“…Previously, using microarray hybridization to assess maize (Zea mays) acclimation responses to UV-B, we found that genes encoding protein translation components were the largest functional group up-regulated by UV-B (Casati and Walbot, 2003). On a microarray containing approximately 2,500 distinct maize cDNA types, there was significant up-regulation of 44 transcripts associated with translation or ribosome assembly.…”
mentioning
confidence: 99%